Evaluasi Penggunaan Sistem Informasi dalam Proses Bisnis Perusahaan - Nabila Chairunnisa; Muhammad Irwan Padli Nasution (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This article discusses the evaluation of the use of information systems in business processes within companies, focusing on how information technology can enhance operational efficiency and decision-making. The research employs a qualitative approach involving in-depth interviews and document analysis from several companies that have implemented information systems. The findings indicate that the appropriate use of information systems can accelerate workflows, reduce human errors, and increase data transparency. However, challenges such as resistance to change and lack of training were also identified as hindering factors. The article concludes that to maximize the benefits of information systems, companies need to conduct regular evaluations and provide adequate support for employees. These findings are expected to offer insights for managers and stakeholders in formulating more effective information system implementation strategies.